Book review: Millar, K.M. 2018: Reclaiming the Discarded: Life and Labour on Rio's Garbage Dump. (July 2019) - Rodríguez, Diana Jiménez Thomas
Millar, K.M. 2018: Reclaiming the Discarded: Life and Labour on Rio's Garbage Dump . Durham and London: Duke University Press. xii + 236 pp. £18.99 paper. ISBN: 9780822370505